Inovasi Kurikulum Kebidanan Berbasis Kecerdasan Emosional: Tinjauan Skoping - Nurisna Ummu Hafitasari; Ari Indra Susanti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze the relationship between emotional intelligence (EI) and midwifery service quality and its implications for higher education curricula. A scoping review method was conducted using the Arksey and O'Malley framework and aligned with PRISMA-ScR guidelines. Articles were retrieved from four databases (Scopus, PubMed, ScienceDirect, and Google Scholar) and limited to publications between 2020 and 2025. The data were analyzed using qualitative thematic analysis. The findings consistently demonstrate that EI is positively associated with academic achievement, clinical performance, decision-making, and quality of care, and in several studies functions as a predictor of professional outcomes. Educational strategies such as simulation-based learning, scenario-based approaches, and structured reflective practice were reported to enhance self-awareness, emotional regulation, and professional confidence. The evidence suggests that EI is most effective when integrated longitudinally and embedded within clinical education rather than delivered solely as a stand-alone subject. Systematic integration of EI within midwifery curricula represents a strategic pathway to strengthening professional competence, patient safety, and maternal-neonatal care quality.